Aerogel felt

By preparing aerogel felts with low organic content and using specific preparation methods, the problem of thin insulation materials and insufficient thermal insulation performance in the prior art is solved, and the excellent thermal insulation and mechanical properties of the aerogel felts are achieved, which is suitable for high-temperature environments.

CN119894826APending Publication Date: 2025-04-25LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480004043.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-19
Filing Date
2024-04-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult to develop a thin thermal insulation material with excellent thermal insulation performance in the prior art, and the mechanical strength of the aerogel is insufficient, easy to rupture, and difficult to widely use.

Method used

The thermal insulation and mechanical properties are improved by preparing an aerogel felt containing aerogel and a felt substrate with an organic content of less than 1.2% by weight and using specific preparation methods including sol impregnation, surface modification and heat treatment.

Benefits of technology

It realizes the excellent thermal insulation performance and mechanical strength of aerogel felt, which can effectively prevent fires and fire spread, and is suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894826A_ABST
    Figure CN119894826A_ABST
Patent Text Reader

Abstract

The present invention relates to an aerosol felt, a heat-insulating member comprising the aerogel felt, a battery comprising the heat-insulating member, and a method for manufacturing the aerogel felt, in which the aerogel felt contains an aerogel and a felt base material and has an organic content of 1.2% by weight or less, to a heat-insulating member comprising the aerogel felt, to a battery comprising the heat-insulating member, and to a method for manufacturing the aerogel felt. The aerogel felt provided by the invention has low organic matter content, and shows excellent heat absorption and fire extinguishing properties, so that the aerogel felt can effectively control the occurrence and spreading of fire disasters when being used in various products.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0051229 filed in the Korean Intellectual Property Office on April 19, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The invention relates to an aerogel felt containing aerogel with low organic matter content, and a method for preparing the aerogel felt. Background Art

[0004] Electronic products such as laptops, OLEDs, or TVs have hot spots caused by heat sources, which may reduce the emotional quality perceived by consumers due to partial heat dissipation from the surface of the device. In addition, if the heat is not properly diffused to the outside due to the use of simple thermal insulation materials, the excessive accumulation of heat may cause system failure, shorten the life of the product, or even cause an explosion or fire. In order to solve the problems caused by this heat generation, various thermal insulation materials have been applied, but so far, the best thermal insulation material that is thin and has excellent thermal insulation performance has not been developed, so various research and technology development are being carried out on thermal insulation.

[0005] In order to solve the above typical problems, there is a case where aerogel is applied, and aerogel is attracting attention as a highly efficient thermal insulation material. Aerogel is a highly porous material composed of nanoparticles, and has high porosity, large specific surface area and low thermal conductivity, so it is attracting attention due to its use as a highly efficient thermal insulation material, sound insulation material, etc.

[0006] However, due to its complicated preparation process and its high preparation cost, aerogel is only used for extremely limited purposes despite its excellent material properties. In addition, due to its high porosity, aerogel has poor mechanical strength, so there is a disadvantage that aerogel is easily broken even by a slight impact. Therefore, in recent years, aerogel felt composite technology has been studied to make up for the above shortcomings of aerogel itself and enable it to be processed in various forms.

[0007] Aerogel felt is an aerogel material that has been compounded and made into a mat or sheet form, and has the characteristics of being bendable, foldable or cut due to its flexibility. Therefore, aerogel felt can be applied to pipe insulation materials, clothing, etc., and it can also be used in various industrial applications. Since aerogel felt is a composite composed of fibers and aerogel, it has flexibility. The fibers play a role in enhancing the flexibility and mechanical strength of the aerogel felt, and the aerogel imparts thermal insulation properties due to its porosity. The key composite technology of aerogel felt is to composite the characteristics of the fibers with the characteristics of the aerogel to strengthen the advantages of the fibers and aerogel and make up for their shortcomings. This aerogel felt is a new material that has better heat resistance and thermal insulation than polystyrene foam or polyurethane foam as conventional polymer insulation materials, and has attracted attention as a high-tech material that can solve energy-saving and environmental problems that will be developed in the future.

[0008] Meanwhile, such aerogel has very low mechanical strength due to its porous structure, and therefore an aerogel composite is prepared and used by impregnating and combining fibers such as inorganic fibers or organic fibers, which are conventional thermal insulation fibers, with the aerogel, and the adhesion between the fibers and the aerogel of the aerogel composite is weak, so that the aerogel particles are separated during processing steps such as cutting and bending, thereby generating dust and deteriorating durability, which may cause damage to the device, etc. when the aerogel composite is used as a thermal insulation material for electronic products.

[0009] Therefore, there is an urgent need to develop a material that can prevent the flame caused by fire and explosion of battery modules and battery packs from spreading to adjacent battery modules regardless of the capacity of the battery and the increase in the size of the battery modules and battery packs. Summary of the invention

[0010] Technical issues

[0011] An object of the present invention is to provide an aerogel felt that can be used in products such as batteries to effectively achieve thermal insulation and fire suppression performance, and also provides a thermal insulation component including the aerogel felt.

[0012] Technical Solution

[0013] In order to achieve the above-mentioned object, the present invention provides an aerogel felt, a thermal insulation component comprising the aerogel felt, a battery comprising the thermal insulation component, and a method for preparing the aerogel felt.

[0014] (1) The present invention provides an aerogel felt comprising an aerogel and a felt substrate, wherein the organic matter content according to the following equation 1 is 1.2 wt % or less.

[0015] [Equation 1]

[0016] Organic matter content (weight %) = [(Wa-Wb) / Wa] × 100

[0017] In the above Equation 1, Wa is the weight (g) of the aerogel felt before heat treatment, and Wb is the weight (g) of the aerogel felt after heat treatment at 600° C. for 12 hours.

[0018] (2) In the above (1), the present invention provides an aerogel felt, wherein the organic matter is one or more selected from the group consisting of a hydrophobic group bonded to the aerogel, a binder, and a sizing agent.

[0019] (3) In the above (1) or (2), the present invention provides an aerogel felt, wherein the room temperature thermal conductivity of the aerogel felt is 15 mW / mK to 35 mW / mK.

[0020] (4) In any one of the above (1) to (3), the present invention provides an aerogel felt, wherein the aerogel contains pores with a pore size of 10 nm to 50 nm.

[0021] (5) In any one of the above (1) to (4), the present invention provides an aerogel felt, wherein the felt substrate is one or more selected from the group consisting of a film, a sheet, a mesh, a fiber, a porous body, a foam body and a non-woven fabric body.

[0022] (6) In the above (5), the present invention provides an aerogel felt, wherein the felt substrate is one or more selected from the group consisting of glass fiber, ceramic wool, basalt fiber and ceramic paper.

[0023] (7) In any one of the above (1) to (6), the present invention provides an aerogel felt, wherein the moisture impregnation rate of the aerogel felt according to the following equation 2 is 100 weight % or more:

[0024] [Equation 2]

[0025] Water impregnation rate (weight %) = [(Wc-Wd) / Wd] × 100

[0026] In the above Equation 2, Wc is the weight (g) of the aerogel felt after being immersed in distilled water at 21±2° C. for 15 minutes, and Wd is the weight (g) of the aerogel felt before being immersed.

[0027] (8) In any one of the above (1) to (7), the present invention provides an aerogel felt, wherein the heat of combustion of the aerogel felt according to the ISO 1716 measurement method is 200 cal / g or less.

[0028] (9) In any one of the above (1) to (8), the present invention provides an aerogel felt, wherein the aerogel felt is prepared by a preparation method comprising the following steps: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol, and gelling the sol to prepare a wet gel felt; 3) surface modifying the wet gel felt; 4) drying the surface-modified wet gel felt; and 5) heat-treating the dried wet gel felt at a temperature of 450°C to 650°C for 10 minutes to 6 hours.

[0029] (10) In any one of the above (1) to (9), the present invention provides an aerogel felt, wherein the aerogel felt is prepared by a preparation method comprising the following steps: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol, and gelling the sol to prepare a wet gel felt; and 3) drying the wet gel felt, wherein the felt substrate is pretreated at a temperature of 400°C to 500°C for 30 minutes to 2 hours, and does not include surface treatment of the wet gel felt.

[0030] (11) The present invention provides a thermal insulation component comprising the aerogel felt according to any one of (1) to (10) above.

[0031] (12) The present invention provides a battery comprising the heat insulating component of (11) above.

[0032] (13) The present invention provides an aerogel felt comprising an aerogel and a felt substrate, wherein the compression rate of the aerogel felt according to the following equation 3 is 15% to 30%.

[0033] [Equation 3]

[0034] Compression ratio (%) = [(Ta-Tb) / Ta] × 100

[0035] In the above Equation 3, Ta is the thickness (mm) of the aerogel felt before compression, and Tb is the thickness (mm) of the aerogel felt after compression at 350 kPa.

[0036] Beneficial Effects

[0037] The aerogel felt of the present invention has a low organic matter content, thereby exhibiting excellent heat absorption and fire extinguishing effects, so the aerogel felt can be used in products to effectively play the function of preventing the occurrence and spread of fire. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Graphs showing the pore distribution of the aerogel felt of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0039] Hereinafter, the present invention will be described in more detail for understanding of the present invention.

[0040] It will be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to having the meaning defined in the commonly used dictionary. It will be further understood that based on the inventors can appropriately define the meaning of the words or terms to best explain the principles of the present invention, the words or terms should be interpreted as having the meaning consistent with its meaning in the context of the relevant field and the technical concept of the present invention.

[0041] Hereinafter, the present invention will be described in detail.

[0042] The aerogel felt of the present invention comprises an aerogel and a felt substrate, wherein the organic matter content according to the following equation 1 is 1.2 wt % or less.

[0043] [Equation 1]

[0044] Organic matter content (weight %) = [(Wa-Wb) / Wa] × 100

[0045] In the above Equation 1, Wa is the weight (g) of the aerogel felt before heat treatment, and Wb is the weight (g) of the aerogel felt after heat treatment at 600° C. for 12 hours.

[0046] Conventional aerogel felt is prepared by a hydrophobization process using a surface modification step, and therefore inevitably contains organic matter above a predetermined content. If such an aerogel felt is exposed to high temperature and high energy conditions, the hydrophobic groups on its surface introduced during the surface modification process burn, resulting in flames, odors, and heat. The above phenomenon has become a reason for limiting the temperature range in which aerogel felt can be used for thermal insulation components, etc., and in particular, there are the following limitations: aerogel felt cannot be used for batteries, etc. that need to be used under ultra-high temperature conditions above 1000°C, or even if used, the performance of the aerogel felt is significantly deteriorated.

[0047] On the other hand, as described above, the aerogel felt of the present invention is characterized by a low organic matter content. This indicates that the aerogel felt of the present invention contains a small amount of hydrophobic groups, thereby suppressing phenomena such as heat generation at high temperatures caused by the hydrophobic groups, which makes the aerogel felt of the present invention different from conventional aerogel felts and can be used for thermal insulation components, etc. even in extreme environments with very high temperatures.

[0048] In the present invention, the organic matter may be one or more selected from the group consisting of a hydrophobic group bonded to the aerogel, a binder, and a sizing agent. More specifically, the hydrophobic group may be an alkyl group, such as a methyl group or an ethyl group, and the binder and the sizing agent may be polystyrene, polybutyl acrylate, polyvinyl alcohol, polyester, polyurethane, epoxy resin, acrylic resin, or a combination thereof, but not limited thereto.

[0049] In the present invention, the room temperature thermal conductivity of the aerogel felt may be 15 mW / mK to 35 mW / mK, specifically 18 mW / mK to 30 mW / mK or 20 mW / mK to 25 mW / mK.

[0050] The aerogel felt of the present invention has excellent high-temperature thermal insulation performance while maintaining the appropriate thermal conductivity as described above.

[0051] In the present invention, the aerogel contained in the aerogel felt may include pores having a pore diameter of 10 nm to 50 nm.

[0052] In the present invention, the water impregnation rate of the aerogel felt according to the ASTM C1511 measurement method may be 100 wt % or more, specifically 150 wt % or more. Specifically, the water impregnation rate may be calculated according to the following equation 2.

[0053] [Equation 2]

[0054] Water impregnation rate (weight %) = [(Wc-Wd) / Wd] × 100

[0055] In the above Equation 2, Wc is the weight (g) of the aerogel felt after being immersed in distilled water at 21±2° C. for 15 minutes, and Wd is the weight (g) of the aerogel felt before being immersed.

[0056] The aerogel felt of the present invention has a low organic matter content and thus a low hydrophobicity, and at the same time, can exhibit a high water impregnation rate as described above.

[0057] In the present invention, the heat of combustion of the aerogel felt according to the ISO 1716 measurement method may be 200 cal / g or less, more specifically 150 cal / g or less, 100 cal / g or less, or 70 cal / g or less.

[0058] Compared with conventional aerogel felts, the aerogel felt of the present invention exhibits very low combustion heat, and therefore, when exposed to high temperatures, the heat energy released while burning is low, which can minimize heat generation, and therefore, the aerogel felt of the present invention exhibits excellent thermal insulation performance.

[0059] In the present invention, the compression rate of the aerogel felt according to the following Equation 3 may be 15% to 30%, specifically 15% to 29%, or 16% to 28%.

[0060] [Equation 3]

[0061] Compression ratio (%) = [(Ta-Tb) / Ta] × 100

[0062] In the above Equation 3, Ta is the thickness (mm) of the aerogel felt before compression, and Tb is the thickness (mm) of the aerogel felt after compression at 350 kPa.

[0063] Specifically, the compression ratio can be obtained by preparing an aerogel felt sample, such as a 10 cm×10 cm aerogel felt sample, applying a pressure of 350 kPa to the sample using a UTM device, and then comparing the thickness before and after the pressure is applied.

[0064] Since the aerogel felt of the present invention exhibits excellent strength and pressure resistance, its thickness reduction due to pressure is suppressed, and thus the aerogel felt can exhibit a low compressibility as described above.

[0065] In the present invention, the felt substrate may be one or more selected from the group consisting of a film, a sheet, a net, a fiber, a porous body, a foam body, and a nonwoven fabric body, and may be a laminate of two or more thereof.

[0066] In addition, the felt substrate may have surface roughness or be patterned on its surface according to its use. Specifically, the felt substrate may be a fiber that can further improve thermal insulation performance by including spaces or voids so that sol is easily inserted inside the felt substrate and aerogel is easily formed, and may have low thermal conductivity.

[0067] Specifically, the felt substrate can be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (polyethylene, polypropylene, copolymers thereof, etc.), cellulose, carbon, cotton, wool, linen, non-woven fabrics, glass fiber, ceramic wool, basalt fiber, ceramic paper, etc., more specifically, it can be glass fiber, ceramic wool, basalt fiber, ceramic paper or a combination thereof as an inorganic fiber series, but is not limited to this.

[0068] In addition, the aerogel felt of the present invention may be contained in a heat insulating member, and the heat insulating member may be contained in a battery and used.

[0069] The aerogel felt of the present invention can be prepared using the following preparation method.

[0070] Specifically, the first aspect of the present invention includes: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol, and gelling the sol to prepare a wet gel felt; 3) surface modifying the wet gel felt; 4) drying the surface-modified wet gel felt; and 5) heat-treating the dried wet gel felt at a temperature of 450°C to 650°C for 10 minutes to 6 hours.

[0071] In addition, the second aspect of the present invention includes: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol and gelling the sol to prepare a wet gel felt; and 3) drying the wet gel felt, wherein the felt substrate is pretreated at a temperature of 400°C to 500°C for 30 minutes to 2 hours, and the second aspect does not include surface treatment of the wet gel felt.

[0072] [Implementation Method 1]

[0073] Step 1)

[0074] Step 1) is a step of preparing a sol containing a precursor material and a catalyst composition, and the sol can be prepared by mixing the precursor material and the catalyst composition.

[0075] According to one embodiment of the present invention, the sol in the present invention may be, for example, a silica sol, and when the sol is a silica sol, the precursor material may be a silica precursor.

[0076] At this time, the silicon dioxide precursor can be an alkoxy compound containing silicon, and can be specifically a tetraalkyl silicate, such as tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate and tetra(dodecyl) orthosilicate. More specifically, the silicon dioxide precursor can be tetraethyl orthosilicate (TEOS), and at this time, tetraethyl orthosilicate can be more preferably prehydrolyzed tetraethyl orthosilicate (prehydrolyzed TEOS, HTEOS).

[0077] HTEOS is a polyethyl silicate oligomer material with a wide molecular weight distribution. When HTEOS is synthesized from TEOS monomers in oligomer form, physical properties such as gelation time can be adjusted, so that HTEOS can be easily applied according to the user's reaction conditions. In addition, the advantage is that the final product can produce reproducible physical properties.

[0078] That is, HTEOS refers to partially hydrated polyethyl silicate oligomers, particularly oligomers derived from partially hydrated TEOS.

[0079] The amount of silica precursor used can be such that the content of silica contained in the silica sol is 0.1 wt % to 30 wt %, but is not limited thereto. If the content of silica satisfies the above range, it is preferred in terms of ensuring that the mechanical physical properties (especially flexibility) of the aerogel felt are at an excellent level while having an improved thermal insulation effect.

[0080] In addition, the catalyst composition may include an organic solvent, water, and an alkali catalyst. In this case, the alkali catalyst may include an inorganic base such as sodium hydroxide or potassium hydroxide, or an organic base such as ammonium hydroxide, but is not limited thereto.

[0081] Specifically, the organic base can be ammonium hydroxide (NH4OH), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine or dibutanolamine, and a mixture of two or more thereof can be used. More specifically, the base catalyst can be NaOH.

[0082] In addition, the organic solvent may be specifically an alcohol, in which case the alcohol may be a monohydric alcohol such as methanol, ethanol, isopropanol and butanol; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol and sorbitol, and any one thereof or a mixture of two or more thereof may be used. Among them, when considering the miscibility with water and aerogel, the alcohol may be a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol and butanol, and may be, for example, ethanol.

[0083] Taking into account the hydrophobicity of the aerogel finally prepared and promoting the surface modification reaction, those skilled in the art may use the alcohol (polar organic solvent) as described above in an appropriate amount.

[0084] According to one embodiment of the present invention, the content of the catalyst composition can make the pH of the sol be 4 to 8. When the content makes the pH of the sol meet the above range, gelation can be easily and effectively achieved. In addition, the catalyst composition is added in a liquid phase in which the alkali catalyst is diluted in water and an organic solvent, thereby preventing the problem of catalyst precipitation.

[0085] Step 2)

[0086] Step 2) is a step of impregnating a felt substrate with the sol and gelling the sol to prepare a wet gel felt.

[0087] In the present invention, gelation can form a network structure from the precursor material, wherein the network structure can be a planar mesh structure formed by specific polygons with more than one atomic arrangement connected to each other, or can be a structure in which specific polyhedrons share their vertices, edges, faces, etc. to form a three-dimensional skeleton structure.

[0088] The gelation of the sol can occur in a state where the felt base material is impregnated with the sol.

[0089] The impregnation may be performed in a reaction vessel capable of accommodating the felt substrate, and the impregnation may be performed by pouring the sol into the reaction vessel, or by placing the felt substrate into the reaction vessel containing the sol to wet the felt substrate. At this time, in order to improve the bonding of the felt substrate with the sol, the felt substrate may be gently pressed down to fully impregnate. Thereafter, the felt substrate may be pressed to a predetermined thickness under a constant pressure to remove excess sol, thereby shortening the subsequent drying time.

[0090] According to one embodiment of the present invention, the felt substrate can be a film, a sheet, a net, a fiber, a porous body, a foam, a nonwoven fabric body or a laminate of two or more layers thereof. In addition, depending on its use, the felt substrate can form a surface roughness or be patterned on its surface. Specifically, the felt substrate can be a fiber that can further improve thermal insulation performance by including space or voids, thereby making it easy to form an aerosol inside the felt substrate, and can have low thermal conductivity.

[0091] Specifically, the felt substrate can be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (polyethylene, polypropylene, copolymers thereof, etc.), cellulose, carbon, cotton, wool, linen, non-woven fabrics, glass fiber, ceramic wool, basalt fiber, ceramic paper, etc., more specifically, it can be glass fiber, ceramic wool, basalt fiber or ceramic paper as an inorganic fiber series, but is not limited to this.

[0092] In addition, after the above step 2), a step of aging the wet gel felt may be further included.

[0093] An aging step can be further performed as a process of allowing the chemical changes to be fully realized by leaving the silica wet gel or silica wet gel felt to stand at a suitable temperature, and the aging step can make the formed network structure more firmly formed, thereby enhancing the mechanical stability of the silica aerogel or silica aerogel felt of the present invention.

[0094] The aging step of the present invention is performed by adding a solution of a basic catalyst such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, pyridine, etc. diluted in an organic solvent at a concentration of 1% to 10%. Therefore, the Si-O-Si bond in the aerogel is induced to the maximum extent to make the network structure of the silica gel stronger, thereby having the effect of helping to maintain the pore structure in the subsequent rapid drying process. At this time, the organic solvent can be the above-mentioned alcohol (polar organic solvent), specifically, it can include ethanol.

[0095] In addition, the aging step should be performed within a suitable temperature range to enhance the optimal pore structure, and the aging step of the present invention can be performed by leaving the wet gel felt at a temperature of 30° C. to 70° C. for 1 hour to 24 hours. If the aging temperature is lower than 30° C., the aging time becomes too long, which may result in an increase in the total process time, thereby possibly causing a problem of reduced productivity, and if the aging temperature is higher than 70° C., the temperature exceeds the boiling point of ethanol, thereby possibly causing a problem of increased solvent loss due to evaporation, which may result in an increase in raw material costs.

[0096] Step 3)

[0097] Step 3) is a step of surface modification of the wet gel felt, and can be a step of hydrophobizing the wet gel felt, especially the silica wet gel felt, with a surface modifier. Specifically, this step can be performed by bonding the hydrophobic groups from the surface modifier to the surface of the silica wet gel.

[0098] In silica aerogel felt, silanol groups (Si-OH) exist on the surface of silica, and the silanol groups absorb water in the air due to their hydrophilicity, so there is a disadvantage that the thermal conductivity gradually increases. Therefore, in order to suppress the absorption of moisture in the air to maintain low thermal conductivity, the surface of the silica aerogel needs to be modified to be hydrophobic in advance.

[0099] As the surface modifier of the present invention, a compound that makes the surface of the wet gel hydrophobic may be used without limitation, and it may be, for example, a silane compound, a siloxane compound, a silanol compound, a silazane compound or a combination thereof.

[0100] Specifically, the surface modifier may be a silane compound such as trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane, trimethylethoxysilane, vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane and 3-aminopropyltriethoxysilane; a siloxane compound such as polydimethylsiloxane, polydiethylsiloxane and octamethylcyclotetrasiloxane; a silane Alcohol compounds such as trimethylsilanol, triethylsilanol, triphenylsilanol and tert-butyldimethylsilanol; silazane compounds such as 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane and 1,2-diisopropyldisilazane, or a combination thereof, and specifically, the surface modifier may be hexamethyldisilazane.

[0101] The surface modifier may be used in the form of a solution diluted in an organic solvent, and the organic solvent may be the alcohol (organic solvent) in step 1), wherein the surface modifier may be diluted to 1 to 10 volume % based on the total volume of the diluted solution.

[0102] In addition, the amount of the surface modifier added can be 0.01 volume % to 10 volume % relative to the wet gel felt. Since the amount of the surface modifier is sufficient within the above range, it can not only have excellent surface modification reactivity, but also promote surface modification, so that the condensation reaction of the unmodified silanol group can be suppressed during the drying process, so that the final produced silica aerogel felt has a more excellent porosity.

[0103] The above step 3) can be performed by adding the surface modifier at a temperature of 50° C. to 90° C., preferably 50° C. to 80° C., for 1 hour to 24 hours.

[0104] Step 4)

[0105] Step 4) is a step of drying the surface-modified wet gel felt, and by removing water and solvent in the wet gel felt, an aerogel felt can be prepared.

[0106] At the same time, the preparation method of one embodiment of the present invention can also perform a washing step before drying. Washing is a step to remove impurities (sodium ions, unreacted substances, by-products, etc.) generated during the reaction and residual ammonia that can react with CO2 to produce ammonium carbonate salts during supercritical drying to obtain a high-purity hydrophobic silica aerogel, and can be performed by a dilution process or an exchange process using a non-polar organic solvent.

[0107] The drying step of one embodiment of the present invention may be performed by a process of removing the solvent while maintaining the pore structure of the aged gel, and the drying step may be performed by a supercritical drying process or an atmospheric drying process.

[0108] The supercritical drying process can be carried out using supercritical carbon dioxide. Carbon dioxide (CO2) is in a gaseous state at room temperature and atmospheric pressure, but when the temperature and pressure exceed a predetermined limit of temperature and pressure called the supercritical point, the evaporation process does not occur, so that the carbon dioxide becomes in a critical state where gas and liquid cannot be distinguished, and the carbon dioxide in the critical state is called supercritical carbon dioxide.

[0109] Supercritical carbon dioxide has a molecular density close to that of a liquid, but a low viscosity, so that its properties are similar to those of a gas, and has a high diffusion rate and high thermal conductivity, so the drying efficiency is high and the drying process time can be shortened.

[0110] Specifically, the supercritical drying process performs the following solvent replacement process: the aged wet gel felt is placed in a supercritical drying reactor, and then liquid CO2 is filled therein, and then the alcohol solvent inside the wet gel is replaced with CO2. Thereafter, the temperature is raised to 40°C to 70°C at a predetermined heating rate (specifically 0.1°C / min to 1°C / min), and the pressure greater than or equal to the pressure at which the carbon dioxide becomes supercritical (specifically a pressure of 100 bar to 150 bar) is maintained to keep the carbon dioxide in a supercritical state for a predetermined period of time (specifically 20 minutes to 1 hour). Typically, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. The carbon dioxide is maintained at a predetermined temperature and a predetermined pressure to maintain a supercritical state for 2 hours to 12 hours, more specifically 2 hours to 6 hours, and the pressure is gradually reduced to complete the supercritical drying process, thereby preparing an aerogel felt.

[0111] In addition, the atmospheric drying process may be performed according to a conventional method, such as hot air drying at a temperature of 70° C. to 200° C. and atmospheric pressure (1±0.3 atm), IR drying, and the like.

[0112] As a result of the above-mentioned drying process, a felt containing a porous aerogel having nano-sized pores can be manufactured. In particular, the silica aerogel of one embodiment of the present invention has excellent physical properties (especially low tap density and high porosity) and a high degree of hydrophobicity, and the silica aerogel-containing felt containing the silica aerogel has excellent mechanical flexibility and low thermal conductivity.

[0113] Furthermore, before or after the drying step, a compression step for controlling the thickness and making the internal structure and surface shape of the felt uniform, a molding step for having a suitable shape or form according to the application, or a lamination step for laminating separate functional layers may be further performed.

[0114] Step 5)

[0115] Step 5) is a step of performing heat treatment at a temperature of 450° C. to 650° C. for 10 minutes to 6 hours, wherein the aerogel felt is exposed to high temperature under predetermined conditions to remove organic matter.

[0116] By heat treating at the above temperature, excessive shrinkage of silicon dioxide due to excessively high temperature can be prevented, and organic matter can be fully decomposed by appropriate high temperature. Within the above range, those skilled in the art can use an appropriate combination of temperature and time for heat treatment.

[0117] In addition, the strength of the aerogel felt can be improved by sintering the silicon dioxide in the aerogel felt through heat treatment.

[0118] As such, since organic matter is removed through the heat treatment process as described above, the aerogel felt of the present invention has a low organic matter content of 1.2 wt % or less, but exhibits high strength and thus can have a lower compression rate than conventional aerogel felt.

[0119] [Implementation Method 2]

[0120] Step 1)

[0121] Step 1) is a step of preparing a sol containing a precursor material and a catalyst composition, and the sol can be prepared by mixing the precursor material and the catalyst composition.

[0122] According to one embodiment of the present invention, the sol in the present invention may be, for example, a silica sol, and when the sol is a silica sol, the precursor material may be a silica precursor.

[0123] At this time, the silicon dioxide precursor can be an alkoxy compound containing silicon, and can be specifically a tetraalkyl silicate, such as tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetra-sec-butyl orthosilicate, tetra-tert-butyl orthosilicate, tetrahexyl orthosilicate, tetracyclohexyl orthosilicate and tetra(dodecyl) orthosilicate. More specifically, the silicon dioxide precursor can be tetraethyl orthosilicate (TEOS), and at this time, tetraethyl orthosilicate can be more preferably prehydrolyzed tetraethyl orthosilicate (prehydrolyzed TEOS, HTEOS).

[0124] HTEOS is a polyethyl silicate oligomer material with a wide molecular weight distribution. When HTEOS is synthesized from TEOS monomers in oligomer form, physical properties such as gelation time can be adjusted, so that HTEOS can be easily applied according to the user's reaction conditions. In addition, the advantage is that the final product can produce reproducible physical properties.

[0125] That is, HTEOS refers to partially hydrated polyethyl silicate oligomers, particularly oligomers derived from partially hydrated TEOS.

[0126] The amount of silica precursor used can be such that the content of silica contained in the silica sol is 0.1 wt % to 30 wt %, but is not limited thereto. If the content of silica satisfies the above range, it is preferred in terms of ensuring that the mechanical physical properties (especially flexibility) of the aerogel felt are at an excellent level while having an improved thermal insulation effect.

[0127] In addition, the catalyst composition may include an organic solvent, water and an alkaline catalyst. In this case, the alkaline catalyst may be an inorganic base such as sodium hydroxide and potassium hydroxide, or an organic base such as ammonium hydroxide. However, in the case of an inorganic base, the metal ions contained in the compound can coordinate with the Si-OH compound, so an organic base may be preferred.

[0128] Specifically, the organic base can be ammonium hydroxide (NH4OH), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyldiethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine or dibutanolamine, and a mixture of two or more thereof can be used. More specifically, the base catalyst can be ammonium hydroxide (NH4OH).

[0129] In addition, the organic solvent may be specifically an alcohol, in which case the alcohol may be a monohydric alcohol such as methanol, ethanol, isopropanol and butanol; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol and sorbitol, and any one thereof or a mixture of two or more thereof may be used. Among them, when considering the miscibility with water and aerogel, the alcohol may be a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol and butanol, and may be ethanol, for example.

[0130] Taking into account the hydrophobicity of the aerogel finally prepared and promoting the surface modification reaction, those skilled in the art may use the alcohol (polar organic solvent) as described above in an appropriate amount.

[0131] According to one embodiment of the present invention, the content of the catalyst composition can make the pH of the sol be 4 to 8. When the content makes the pH of the sol meet the above range, gelation can be easily and effectively achieved. In addition, the catalyst composition is added in a liquid phase in which the alkali catalyst is diluted in water and an organic solvent, thereby preventing the problem of catalyst precipitation.

[0132] Step 2)

[0133] Step 2) is a step of impregnating a felt substrate with the sol and gelling the sol to prepare a wet gel felt.

[0134] In the present invention, the felt substrate is pretreated at a temperature of 400° C. to 500° C. for 30 minutes to 2 hours. Generally, the felt substrate contains organic matter above a predetermined content, so before preparing the aerogel felt, the organic matter contained in the felt substrate is removed in advance by pretreatment so that the felt substrate can be used.

[0135] By pretreating under the pretreatment conditions within the above range, organic matter in the felt substrate is removed, thereby reducing the content of organic matter in the aerogel felt finally prepared, while achieving excellent high-temperature thermal insulation performance and strength of the aerogel felt.

[0136] In the present invention, gelation can form a network structure from the precursor material, wherein the network structure can be a planar mesh structure formed by specific polygons with more than one atomic arrangement connected to each other, or can be a structure in which specific polyhedrons share their vertices, edges, faces, etc. to form a three-dimensional skeleton structure.

[0137] The gelation of the sol can occur in a state where the felt base material is impregnated with the sol.

[0138] The impregnation may be performed in a reaction vessel capable of accommodating the felt substrate, and the impregnation may be performed by pouring the sol into the reaction vessel, or by placing the felt substrate into the reaction vessel containing the sol to wet the felt substrate. At this time, in order to improve the bonding of the felt substrate with the sol, the felt substrate may be gently pressed down to fully impregnate. Thereafter, the felt substrate may be pressed to a predetermined thickness under a constant pressure to remove excess sol, thereby shortening the subsequent drying time.

[0139] According to one embodiment of the present invention, the felt substrate can be a film, a sheet, a net, a fiber, a porous body, a foam, a nonwoven fabric body or a laminate of two or more layers thereof. In addition, depending on its use, the felt substrate can form a surface roughness or be patterned on its surface. Specifically, the felt substrate can be a fiber that can further improve thermal insulation performance by including space or voids, thereby making it easy to form an aerosol inside the felt substrate, and can have low thermal conductivity.

[0140] Specifically, the felt substrate may be polyamide, polybenzimidazole, polyaramid, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (polyethylene, polypropylene, copolymers thereof, etc.), cellulose, carbon, cotton, wool, hemp, nonwoven fabrics, glass fiber or ceramic wool.

[0141] In addition, after the above step 2), a step of aging the wet gel felt may be further included.

[0142] An aging step can be further performed as a process of allowing the chemical changes to be fully realized by leaving the silica wet gel or silica wet gel felt to stand at a suitable temperature, and the aging step can make the formed network structure more firmly formed, thereby enhancing the mechanical stability of the silica aerogel or silica aerogel felt of the present invention.

[0143] The aging step of the present invention is performed by adding a solution of a basic catalyst such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, pyridine, etc. diluted in an organic solvent at a concentration of 1% to 10%. Therefore, the Si-O-Si bond in the aerogel is induced to the maximum extent to make the network structure of the silica gel stronger, thereby having the effect of helping to maintain the pore structure in the subsequent rapid drying process. At this time, the organic solvent can be the above-mentioned alcohol (polar organic solvent), specifically, it can include ethanol.

[0144] In addition, the aging step should be performed within a suitable temperature range to enhance the optimal pore structure. The aging step of the present invention can be performed by leaving the wet gel felt composite at a temperature of 30°C to 70°C for 1 hour to 10 hours. If the aging temperature is lower than 30°C, the aging time becomes too long, which may lead to an increase in the total process time, thereby there may be a problem of reduced productivity, and if the aging temperature is higher than 70°C, the temperature exceeds the boiling point of ethanol, thereby there may be a problem of increased solvent loss due to evaporation, which may lead to an increase in raw material costs.

[0145] Meanwhile, the second aspect of the present invention does not include surface modification of the wet gel felt. If the aerogel felt is prepared according to the prior art, a surface modification step of replacing the hydroxyl groups on the surface of the wet gel felt with methyl groups is usually performed, by which the surface of the aerogel becomes hydrophobic, but there is a problem that the content of organic matter in the aerogel felt increases during the preparation process.

[0146] Therefore, in the second aspect of the present invention, surface modification is not performed to prevent an increase in the organic matter content.

[0147] Step 3)

[0148] Step 3) is a step of drying the wet gel felt, and by removing water and solvent in the wet gel felt, an aerogel felt can be prepared.

[0149] At the same time, the preparation method of one embodiment of the present invention can also perform a washing step before drying. Washing is a step to remove impurities (sodium ions, unreacted substances, by-products, etc.) generated during the reaction and residual ammonia that can react with CO2 to produce ammonium carbonate salts during supercritical drying to obtain a high-purity hydrophobic silica aerogel, and can be performed by a dilution process or an exchange process using a non-polar organic solvent.

[0150] The drying step of one embodiment of the present invention may be performed by a process of removing the solvent while maintaining the pore structure of the aged gel, and the drying step may be performed by a supercritical drying process or an atmospheric drying process.

[0151] The supercritical drying process can be carried out using supercritical carbon dioxide. Carbon dioxide (CO2) is in a gaseous state at room temperature and atmospheric pressure, but when the temperature and pressure exceed a predetermined limit of temperature and pressure called the supercritical point, the evaporation process does not occur, so that the carbon dioxide becomes in a critical state where gas and liquid cannot be distinguished, and the carbon dioxide in the critical state is called supercritical carbon dioxide.

[0152] Supercritical carbon dioxide has a molecular density close to that of a liquid, but a low viscosity, so that its properties are similar to those of a gas, and has a high diffusion rate and high thermal conductivity, so the drying efficiency is high and the drying process time can be shortened.

[0153] Specifically, the supercritical drying process performs the following solvent replacement process: the aged wet gel felt is placed in a supercritical drying reactor, and then liquid CO2 is filled therein, and then the alcohol solvent inside the wet gel is replaced with CO2. Thereafter, the temperature is raised to 40°C to 70°C at a predetermined heating rate (specifically 0.1°C / min to 1°C / min), and the pressure greater than or equal to the pressure at which the carbon dioxide becomes supercritical (specifically a pressure of 100 bar to 150 bar) is maintained to keep the carbon dioxide in a supercritical state for a predetermined period of time (specifically 20 minutes to 1 hour). Typically, carbon dioxide becomes supercritical at a temperature of 31°C and a pressure of 73.8 bar. The carbon dioxide is maintained at a predetermined temperature and a predetermined pressure to maintain a supercritical state for 2 hours to 12 hours, more specifically 2 hours to 6 hours, and the pressure is gradually reduced to complete the supercritical drying process, thereby preparing an aerogel felt.

[0154] In addition, the atmospheric drying process may be performed according to a conventional method, such as hot air drying at a temperature of 70° C. to 200° C. and atmospheric pressure (1±0.3 atm), IR drying, and the like.

[0155] As a result of the above drying process, a felt containing a porous aerogel having nano-sized pores can be prepared. In particular, the silica aerogel of one embodiment of the present invention has excellent physical properties (especially low tap density and high porosity) and a high degree of hydrophobicity, and the silica aerogel-containing felt containing the silica aerogel has excellent mechanical flexibility and low thermal conductivity.

[0156] Furthermore, before or after the drying step, a compression step for controlling the thickness and making the internal structure and surface shape of the felt uniform, a molding step for having a suitable shape or form according to the application, or a lamination step for laminating separate functional layers may be further performed.

[0157] Example

[0158] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the following Examples are only for illustrating the present invention and are not intended to limit the scope of the present invention.

[0159] Example 1

[0160] Tetraethyl orthosilicate (TEOS) was mixed with water in a molar ratio of 1:4, and ethanol was added thereto in a weight ratio of 1:1 relative to TEOS to prepare a silica precursor solution. In order to promote the hydrolysis of the silica precursor solution, an acid was added so that the pH of the silica precursor solution was below 3, and then stirred for more than 2 hours to prepare a hydrated TEOS solution. Ethanol was added in a weight ratio of 1:4 for ethanol:hydrated TEOS solution to prepare a silica sol. An emulsifier TiO2 and a flame retardant Ultracarb (LKAB) in a weight ratio of 0.2 based on 100 parts by weight of the silica sol were mixed and then stirred for 30 minutes. An alkali catalyst solution (5 wt% NaOH aqueous solution) was added in a volume ratio of 99:1 for silica sol:alkali catalyst solution to prepare a catalytic sol.

[0161] The catalytic sol was impregnated into the fiber and gelled. The gelled wet gel felt was recovered from the reaction vessel, aged in a 10 wt% TMES solution at 60°C for 16 hours, and then surface modified. The prepared wet gel felt was placed in a supercritical extractor, and then CO2 was injected therein, after which the temperature inside the extractor was raised to 60°C over 1 hour, and then supercritical drying was performed at 60°C and 150 bar.

[0162] After the drying was completed, heat treatment was performed in an electric furnace at 650° C. for 10 minutes in a normal air atmosphere to obtain an aerogel felt.

[0163] Examples 2 to 5

[0164] An aerogel felt was prepared in the same manner as in Example 1, except that the temperature and time conditions of the heat treatment were changed as shown in Table 1 below.

[0165] Example 6

[0166] Tetraethyl orthosilicate (TEOS) was mixed with water in a molar ratio of 1:4, and ethanol was added thereto in a weight ratio of 1:1 relative to TEOS to prepare a silica precursor solution. In order to promote the hydrolysis of the silica precursor solution, an acid was added so that the pH of the silica precursor solution was below 3, and then stirred for more than 2 hours to prepare a hydrated TEOS solution. Ethanol was added in a weight ratio of 1:4 for ethanol:hydrated TEOS solution to prepare silica sol. Opaquer TiO2 and flame retardant Ultracarb (LKAB) were mixed in a weight ratio of 0.2 based on 100 parts by weight of silica sol and then stirred for 30 minutes. Alkaline catalyst solution (5 wt% NaOH aqueous solution) was added in a volume ratio of 99:1 for silica sol:alkaline catalyst solution to prepare a catalytic sol.

[0167] Meanwhile, the prepared fibers were heat-treated in an electric furnace at 450° C. for 1 hour in a conventional air atmosphere.

[0168] Thereafter, the catalytic sol was impregnated into the heat-treated fibers and gelled. Without a separate surface modification step, the gelled wet gel felt was placed in a supercritical extractor, into which CO2 was then injected, after which the temperature in the extractor was raised to 60°C over 1 hour, and then supercritical drying was performed at 60°C and 150 bar.

[0169] Comparative Example 1

[0170] Tetraethyl orthosilicate (TEOS) was mixed with water in a molar ratio of 1:4, and ethanol was added thereto in a weight ratio of 1:1 relative to TEOS to prepare a silica precursor solution. In order to promote the hydrolysis of the silica precursor solution, an acid was added so that the pH of the silica precursor solution was below 3, and then stirred for more than 2 hours to prepare a hydrated TEOS solution. Ethanol was added in a weight ratio of 1:4 for ethanol:hydrated TEOS solution to prepare silica sol. Opaquer TiO2 and flame retardant Ultracarb (LKAB) were mixed in a weight ratio of 0.2 based on 100 parts by weight of silica sol and then stirred for 30 minutes. Alkaline catalyst solution (5 wt% NaOH aqueous solution) was added in a volume ratio of 99:1 for silica sol:alkaline catalyst solution to prepare a catalytic sol.

[0171] The catalytic sol was impregnated into the fiber and gelled. The gelled wet gel felt was recovered from the reaction vessel, aged in a 10 wt% TMES solution at 60°C for 16 hours, and then surface modified. The prepared wet gel felt was placed in a supercritical extractor, and then CO2 was injected therein, after which the temperature inside the extractor was raised to 60°C over 1 hour, and then supercritical drying was performed at 60°C and 150 bar.

[0172] Comparative Examples 2 and 4

[0173] An aerogel felt was prepared in the same manner as in Example 1, except that the temperature and time conditions of the heat treatment were changed as shown in Table 1 below.

[0174] Comparative Example 3

[0175] Tetraethyl orthosilicate (TEOS) was mixed with water in a molar ratio of 1:4, and ethanol was added thereto in a weight ratio of 1:1 relative to TEOS to prepare a silica precursor solution. In order to promote the hydrolysis of the silica precursor solution, an acid was added so that the pH of the silica precursor solution was below 3, and then stirred for more than 2 hours to prepare a hydrated TEOS solution. Ethanol was added in a weight ratio of 1:4 for ethanol:hydrated TEOS solution to prepare silica sol. Opaquer TiO2 and flame retardant Ultracarb (LKAB) were mixed in a weight ratio of 0.2 based on 100 parts by weight of silica sol and then stirred for 30 minutes. Alkaline catalyst solution (5 wt% NaOH aqueous solution) was added in a volume ratio of 99:1 for silica sol:alkaline catalyst solution to prepare a catalytic sol.

[0176] Meanwhile, the prepared fibers were heat-treated in an electric furnace at 450° C. for 1 hour in a conventional air atmosphere.

[0177] The catalytic sol was impregnated into the heat-treated fiber and gelled. The gelled wet gel felt was recovered from the reaction vessel, aged in a 10 wt% TMES solution at 60°C for 16 hours, and then surface modified. The prepared wet gel felt was placed in a supercritical extractor, and then CO2 was injected therein, after which the temperature inside the extractor was raised to 60°C over 1 hour, and then supercritical drying was performed at 60°C and 150 bar.

[0178] [Table 1]

[0179] Felt pretreatment Surface modification Heat treatment conditions Example 1 X O 650℃, 10min Example 2 X O 650℃, 3 hours Example 3 X O 650℃, 6 hours Example 4 X O 550℃, 10min Example 5 X O 450℃, 3 hours Example 6 450℃, 1 hour X X Comparative Example 1 X O X Comparative Example 2 X O 450℃, 10min Comparative Example 3 450℃, 1 hour O X Comparative Example 4 X O 350℃, 10min

[0180] Experimental Example 1: Organic Matter Content

[0181] The weight (Wa) of the aerogel felt sample with a size of 10 cm×10 cm was measured, and then it was heat-treated at 600° C. for more than 12 hours in a normal air atmosphere to remove all organic matter, and then the weight (Wb) was measured. Finally, the content of organic matter was calculated according to the following equation 1.

[0182] [Equation 1]

[0183] Organic matter content (weight %) = [(Wa-Wb) / Wa] × 100

[0184] [Table 2]

[0185] Organic matter content (weight %) Example 1 0.90 Example 2 0.05 Example 3 0.01 Example 4 1.0 Example 5 0.1 Example 6 1.2 Comparative Example 1 8.5 Comparative Example 2 2.7 Comparative Example 3 5.3 Comparative Example 4 4.8

[0186] As shown in Table 2 above, it has been confirmed that the aerogel felt of the present invention has a low organic content of 1.2 wt % or less, and the aerogel felts of Comparative Examples 1 to 4 have an organic content of more than 2.0 wt %.

[0187] This is because, when the aerogel felts in Examples 1 to 6 were prepared, high-temperature heat treatment was performed, or the fibers were pretreated and used, but surface modification was not performed, thus showing a lower residual organic matter content in the aerogel felt.

[0188] Experimental Example 2: Thermal conductivity at room temperature

[0189] Using a 30 cm×30 cm sample of the silica aerogel felt prepared in each of the Examples and Comparative Examples, thermal conductivity at room temperature (20±5° C.) was measured using an HFM 436 apparatus manufactured by NETZSCH.

[0190] [Table 3]

[0191] Room temperature thermal conductivity (mW / mK) Example 1 21.1 Example 2 21.6 Example 3 24.8 Example 4 21.2 Example 5 22.8 Example 6 20.0 Comparative Example 1 18.3 Comparative Example 2 19.1 Comparative Example 3 18.4 Comparative Example 4 18.7

[0192] As shown in Table 3 above, although the aerogel felt according to the embodiment of the present invention is prepared through a high-temperature heat treatment process, the aerogel felt can maintain a conventional level of thermal conductivity and has higher thermal conductivity and more excellent high-temperature thermal insulation performance than the comparative example.

[0193] Experimental Example 3: High temperature thermal insulation performance

[0194] A 3 mm thick sample of each silica aerogel felt prepared in the examples and comparative examples was made into a size of 10 cm×10 cm. The temperature of the upper heating plate was heated to 650°C. The measurement sample was placed on a lower sample plate equipped with a thermocouple, and the height was adjusted so that the heating plate was in contact with the upper part of the sample. The temperature (back temperature) and time of the lower end of the sample were recorded immediately after contact, and the time (seconds) taken to reach 180°C was measured.

[0195] [Table 4]

[0196] High temperature insulation performance (seconds) Example 1 1245 Example 2 1570 Example 3 1845 Example 4 990 Example 5 1450 Example 6 900 Comparative Example 1 645 Comparative Example 2 820 Comparative Example 3 750 Comparative Example 4 770

[0197] As shown in Table 4 above, it has been confirmed that the aerogel felt of the examples of the present invention has excellent thermal insulation performance at high temperatures, and therefore, the time taken for the aerogel felt to reach 180° C. is longer than that of the comparative examples.

[0198] Experimental Example 4: Compression Resistance

[0199] The samples of each silica aerogel felt prepared in the above-mentioned embodiments and comparative examples were made into a size of 10 cm×10 cm to measure its thickness (Ta). A pressure of 350 kPa was applied to the sample using a UTM device, and the thickness of the sample during compression (Tb) was measured. The difference between the initial thickness and the thickness during compression was divided by the initial thickness to calculate the compression rate (%) according to the following equation 3.

[0200] [Equation 3]

[0201] Compression ratio (%) = [(Ta - Tb) / Ta] × 100

[0202] [Table 5]

[0203] Compression rate at 350kPa pressure (%) Example 1 25 Example 2 20 Example 3 16 Example 4 27 Example 5 22 Example 6 28 Comparative Example 1 40 Comparative Example 2 33 Comparative Example 3 35 Comparative Example 4 38

[0204] As shown in Table 5 above, it has been confirmed that after heat treatment, the aerogel felt of the embodiment of the present invention has improved strength and improved thickness reduction rate (compression ratio) when compressed, and thus has improved compressive resistance.

[0205] Experimental Example 5: Water impregnation rate

[0206] According to ASTM C1511, a specimen with dimensions of 25.4 cm × 25.4 cm was floated on distilled water at 21 ± 2 °C, and a 6.4 mm mesh sieve was placed on the specimen to sink the specimen 127 mm below the water surface. After 15 minutes, the sieve was removed. When the specimen rose to the surface, the specimen was picked up with a clamp and vertically suspended for 60 ± 5 seconds, and then the weights of the specimen before and after impregnation were measured respectively to confirm the weight increase rate, and the weight increase rate was expressed as the water impregnation rate.

[0207] [Table 6]

[0208] Water impregnation rate (weight %) Example 1 180 Example 2 390 Example 3 410 Example 4 155 Example 5 375 Example 6 120 Comparative Example 1 3 Comparative Example 2 45 Comparative Example 3 8 Comparative Example 4 11

[0209] As shown in Table 6 above, it has been confirmed that the aerogel felt of the present invention has a low organic content, and thus has a low degree of hydrophobicity and a high water impregnation rate.

[0210] Experimental Example 6: Pore distribution

[0211] A 0.1 g sample of aerogel felt was placed in a BET special glass cup, connected to a pretreatment device, and then pretreated at 150 °C for 12 hours while reducing the pressure to a pressure of 1 torr to 760 torr to remove impurities containing moisture in the sample. The pore distribution of the pretreated sample was analyzed using a 3FLEX device from Micrometrics based on the absorption / desorption amount of nitrogen according to the partial pressure (0.11 < p / p0 < 1), and is shown in Figure 1 as follows.

[0212] As Figure 1 shown, it has been confirmed that the aerogel of Comparative Example 1 has a small pore diameter of less than 10 nm, while the aerogel of Example 1 has a generally larger pore diameter and a wider distribution due to sintering of the aerogel.

[0213] Experimental Example 7: Measurement of heat of combustion

[0214] The heat of combustion was measured according to the ISO 1716 measurement standard.

[0215] [Table 7]

[0216] Heat of combustion (cal / g) Example 1 1 or less Example 2 1 or less Example 3 1 or less Example 4 56 Example 5 57 Example 6 1 or less Comparative Example 1 1120 Comparative Example 2 240 Comparative Example 3 630

[0217] As shown in Table 7 above, the Examples exhibited very low levels of combustion heat compared to the Comparative Examples. This indicates that when the aerogel felt of the present invention is exposed to high temperatures, heat generation is reduced and high-temperature thermal insulation performance is excellent.

Claims

1. An aerogel felt comprising: Aerogels; and Felt base material, in, The organic content according to the following equation 1 is less than 1.2 wt %: [Equation 1] Organic matter content (weight %) = [(Wa-Wb) / Wa] × 100 Where, in the above equation 1, Wa is the weight in grams of the aerogel felt before heat treatment, and Wb is the weight in g of the aerogel felt after heat treatment at 600° C. for 12 hours.

2. The aerogel blanket according to claim 1, wherein: The organic matter is one or more selected from the group consisting of a hydrophobic group bonded to the aerogel, a binder, and a sizing agent.

3. The aerogel felt according to claim 1, wherein: The room temperature thermal conductivity of the aerogel felt is 15 mW / mK to 35 mW / mK.

4. The aerogel felt according to claim 1, wherein: The aerogel comprises pores with a pore size of 10 nm to 50 nm.

5. The aerogel felt according to claim 1, wherein: The felt substrate is one or more selected from the group consisting of a film, a sheet, a net, a fiber, a porous body, a foam body, and a nonwoven fabric body.

6. The aerogel felt according to claim 5, wherein: The felt substrate is one or more selected from the group consisting of glass fiber, ceramic wool, basalt fiber and ceramic paper.

7. The aerogel felt according to claim 1, wherein: The moisture impregnation rate of the aerogel felt according to the following equation 2 is 100 wt % or more: [Equation 2] Water impregnation rate (weight %) = [(Wc-Wd) / Wd] × 100 Where, in the above equation 2, Wc is the weight in g of the aerogel felt after being immersed in distilled water at 21±2°C for 15 minutes, and Wd is the weight in grams of the aerogel felt before impregnation.

8. The aerogel felt according to claim 1, wherein: The aerogel felt has a heat of combustion of 200 cal / g or less according to the ISO 1716 measurement method.

9. The aerogel felt according to claim 1, wherein: The aerogel felt is prepared by a preparation method comprising the following steps: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol and gelling the sol to prepare a wet gel felt; 3) performing surface modification on the wet gel felt; 4) drying the surface-modified wet gel felt; and 5) heat-treating the dried wet gel felt at a temperature of 450° C. to 650° C. for 10 minutes to 6 hours.

10. The aerogel blanket according to claim 1, wherein: The aerogel felt is prepared by a preparation method comprising the following steps: 1) preparing a sol comprising a precursor material and a catalyst composition; 2) impregnating a felt substrate with the sol and gelling the sol to prepare a wet gel felt; as well as 3) drying the wet gel felt, Wherein, before step 2), the felt substrate is pretreated at a temperature of 400° C. to 500° C. for 30 minutes to 2 hours, and the wet gel felt is not subjected to surface treatment.

11. A thermal insulation component comprising the aerogel felt according to any one of claims 1 to 10.

12. A battery comprising the heat insulating member according to claim 11.

13. An aerogel felt comprising: Aerogels; and Felt base material, in, The compression rate of the aerogel felt according to the following equation 3 is 15% to 30%, [Equation 3] Compression ratio (%) = [(Ta-Tb) / Ta] × 100 In equation 3 above, Ta is the thickness of the aerogel felt before compression in mm, and Tb is the thickness in mm of the aerogel felt after compression at 350 kPa.

Citation Information

Patent Citations

  • Process for preparing quaternized pyridazine derivatives

    KR1020230051229A